Polyculture of tiger shrimp and carps in hardwater seasonal ponds - Athithan, S; Ramanathan, N (Indian Journal of Fisheries, 2011)
Experiments were carried out to assess the growth of tiger shrimp (Penaeus monodon) and carps under polyculture practice particularly in hardwater seasonal ponds. The growth of tiger shrimp and carps were recorded for a period of 110 and 180 days respectively during December, 2002 to May, 2003. The growth rate of Penaeus monodon and carps under polyculture practice were 32g and 298g respectively. The production of shrimp and carps registered under polyculture practice were 25.750 kg/0.1 ha/110 days (a low stocking density of 1.5 nos/m2 ) and 135.450 kg/0.1 ha/180 days respectively.